2014
DOI: 10.1080/15374416.2013.865191
|View full text |Cite
|
Sign up to set email alerts
|

Combining Neural and Behavioral Indicators in the Assessment of Internalizing Psychopathology in Children and Adolescents

Abstract: Anxiety and mood disorders are among the most prevalent mental health problems affecting our youth. We propose that assessment and treatment efforts in this area can benefit from a focus on developmentally sensitive neurobehavioral trait constructs, that is, individual difference constructs with direct referents in both neurobiology and behavior across the lifespan. This approach dovetails with the National Institute of Mental Health's Research Domain Criteria initiative, which aims to improve classification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 94 publications
0
29
1
1
Order By: Relevance
“…Additionally, there is evidence that the ERN‐anxiety association may differ between subclinical and clinical levels of anxiety. For instance, while normative levels of anxiety in children have been associated with a blunted ERN (Meyer, Weinberg, et al, ; Moser et al, ; Torpey et al, ), there is also evidence that enhancement of ERN is already evident in children with clinically significant levels of anxiety (Hajcak et al, ; Ladouceur et al, ; Meyer, Hajcak, et al, ). Moreover, we have recently demonstrated that an enhanced ERN at age 6 predicts a new diagnosis of an anxiety disorder at age 9 (Meyer, Proudfit, Torpey‐Newman, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is evidence that the ERN‐anxiety association may differ between subclinical and clinical levels of anxiety. For instance, while normative levels of anxiety in children have been associated with a blunted ERN (Meyer, Weinberg, et al, ; Moser et al, ; Torpey et al, ), there is also evidence that enhancement of ERN is already evident in children with clinically significant levels of anxiety (Hajcak et al, ; Ladouceur et al, ; Meyer, Hajcak, et al, ). Moreover, we have recently demonstrated that an enhanced ERN at age 6 predicts a new diagnosis of an anxiety disorder at age 9 (Meyer, Proudfit, Torpey‐Newman, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that the association between an enhanced ERN and subclinical levels of trait anxiety does not emerge until adolescence (Meyer, Weinberg, Klein, & Hajcak, 2012). In younger children, heightened trait anxiety may instead relate to a blunted ERN (Meyer, Weinberg, et al, 2012;Moser, Durbin, Patrick, & Schmidt, 2015). Additionally, a blunted ERN has been observed among young, nonanxious children of mothers with anxiety disorders (Torpey et al, 2013).…”
Section: Ern Development Environment and Risk For Psychopathologymentioning
confidence: 99%
“…Child behaviors [10] are coded for anxiety and fear during standardized threat tasks, but these constructs are often referred to interchangeably [10]–[12]. While this aggregate fear/anxiety construct has been linked to familial risk for internalizing disorders in young children (e.g., [13]) and parent-reported child fear and internalizing symptoms [14], it does not discriminate the three distinct threat phases. Similarly, the startle phase is commonly measured using the Fear Potentiated Startle (FPS) technique, where electrodes quantify muscle activity during unpleasant stimuli [8], but this technique cannot be used to assess the other phases of threat response.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, analyses addressing the structure of the PVS will require multiple measures at each unit of analysis to determine whether there is shared construct variance beyond common method variance. Some preliminary work has found promise for these types of models (Moser, Durbin, Patrick, & Schmidt, 2015; Patrick et al, 2013). However, it is critical that multiple assessments from each unit of analysis be available, such that the unit of analysis is not confounded with the construct of interest.…”
Section: Developmental Extensions Of Pvsmentioning
confidence: 99%